Socio-personal variables related to the academic achievement of successful students at the University of the Philippines - Paredes, Ma. Aurora R. 1943- (1968)
The study determined the socio-personal variables related to the academic achievement of successful students at the University of the Philippines. Instruments based on motivation theory were used to identify the socio-personal variables of the students. Identifiable socio-personal variables such as school history, study habits, relationships with teachers and school subject preferences, sibling school performance, nature of family discipline patterns, and students' self decriptions of their job preferences and self-reports on how their teachers describe them related to their academic achievement.
Vita.
Thesis (M. Education)--University of the Philippines, Diliman.
Keywords: University of the Philippines (Diliman) -- Students; Academic schievement -- Philippines -- Diliman (Quezon City).; College students -- Rating of -- Philippines -- Diliman (Quezon City).